Expressive Speech Acts in the Novel "A Midsummer Night's Dream" by William Shakespeare in John Searle's Theory - Pratama, Ilham; Asroriyah, Atik Muhimatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The researcher focused on researching this novel because the dialogue is displayed not only as an aesthetic device, but also as a medium to express conflicts, emotions, and relationship dynamics between characters, especially through expressive speech. This study aims to analyze expressive speech in William Shakespeare's novel "A Midsummer Night's Dream" using John Searle's speech theory of speech. This research explores the role of language in shaping conflicts, conveying emotions, and reflecting social norms and power relations. The method used is qualitative descriptive with content analysis techniques against dialogue excerpts in the novel. The main source of data is obtained from the translated and original version of "A Midsummer Night's Dream". The data analyzed was in the form of dialogue excerpts that contained expressive speech acts. The data collection technique was carried out by purposive sampling to select speech that showed the emotional expression of the characters. The data collection technique is carried out by documentation through reading and recording dialogues. The data analysis technique used the category of expressive speech actions based on the Searle classification. The validity of the data is obtained through triangulation of theories and sources. The research procedure includes the reading of the manuscript, the classification of the dialogue, and the analysis of the meaning of the illocution. The results of the study showed that there were 63 expressive speech acts used to express love, anger, sadness, disappointment, surprise, and other forms of emotion. Characters such as Helena, Hermia, Lysander, and Demetrius became the main users of this act of speech. Expressive speech plays a role in bringing the love triangle conflict to life, depicting gender imbalances, and displaying the emotional transformation of the character. This study concludes that expressive speech acts function as novelistic tools that reinforce characterization, build plots, and reflect cultural values in literary works. These findings contribute to expanding the understanding of the role of language in emotional communication within classical literary texts.